2018
DOI: 10.1111/xen.12396
|View full text |Cite
|
Sign up to set email alerts
|

Human CD31 on porcine cells suppress xenogeneic neutrophil‐mediated cytotoxicity via the inhibition of NETosis

Abstract: These data suggest that human CD31 suppresses neutrophil-mediated xenogenic cytotoxicity via the inhibition of NETosis. As CD31 is widely expressed in a variety of inflammatory cells, human CD31-induced suppression may cover the entire xenogeneic cellular rejection, thus making the generation of human CD31 transgenic pigs very attractive for use in xenografts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…8,9 Most recently, another deleterious immune activation process in xenotransplantation has gained prominence, namely the ejection of DNA-histone complexes into the extracellular space from activated neutrophils to form neutrophil extracellular traps (NETs). 10,11 Increased NET formation is well known in various clinical conditions, including sepsis, trauma, autoimmune diseases, deep vein thrombosis, atherosclerosis, and thrombotic microangiopathy. 12,13 Because multiple nosologies share humoral and cellular activation pathways, we asked whether TAVI increases circulating soluble suppression of tumorigenicity-2 (sST2) and its counterpart interleukin (IL)-33, a known biological alarmin that would serve as an additional biological marker for ongoing inflammatory processes.…”
Section: Central Messagementioning
confidence: 99%
“…8,9 Most recently, another deleterious immune activation process in xenotransplantation has gained prominence, namely the ejection of DNA-histone complexes into the extracellular space from activated neutrophils to form neutrophil extracellular traps (NETs). 10,11 Increased NET formation is well known in various clinical conditions, including sepsis, trauma, autoimmune diseases, deep vein thrombosis, atherosclerosis, and thrombotic microangiopathy. 12,13 Because multiple nosologies share humoral and cellular activation pathways, we asked whether TAVI increases circulating soluble suppression of tumorigenicity-2 (sST2) and its counterpart interleukin (IL)-33, a known biological alarmin that would serve as an additional biological marker for ongoing inflammatory processes.…”
Section: Central Messagementioning
confidence: 99%
“…Wang et al. recently reported that the ectopic expression of human CD31 on porcine cells suppress xenogeneic neutrophil NETosis and cytotoxicity ( 89 ). CD31 (PECAM-1) is well known as an adhesion molecule and is ubiquitously expressed by various inflammatory cells ( 90 ).…”
Section: Inhibition Of Neutrophil-mediated Xenogeneic Rejectionmentioning
confidence: 99%
“…Indeed, neutrophils are activated by pro‐inflammatory cytokines (PMID: 2544300, PMID: 1985637, and PMID: 7601250). To minimize the contribution of neutrophils to graft rejection, Wang et al expressed a neutrophil inhibitory protein in pig cells and evaluated cell survival when cocultured with human neutrophils . Cluster of differentiation 31 (CD31) is a surface transmembrane protein widely expressed on endothelial cells, platelets, and leukocytes.…”
Section: Basic Researchmentioning
confidence: 99%